Prognostic Value of Inflammation and Nutrition-Based Scores in Non-Small Cell Lung Cancer - Erciyestepe, Mert; Selvi, Oğuzhan; Dinç Sonuşen, Şermin; Öztürk, Ahmet Emin; Dinç, Gülhan; Güneş, Tuğçe Kübra; Aydın, Okan; Yaşar, Nurgül; Balkaya Aykut, Gözde; Vatansever, Sezai (Medical principles and practice, 2024)
Abstract Objective: In studies conducted on non-small cell lung cancer (NSCLC) patients, many factors such as age, stage, weight loss, lymph node, and pleural involvement have been shown to affect survival. On the other hand, systemic inflammation plays a critical role in proliferation, migration, invasion, and metastasis. Inflammation and nutrition-based prognostic scores are reported to be associated with survival in patients with NSCLC. The aim of our study is to show the effects of these scores on survival and disease progression in NSCLC patients. Subjects and Methods: Neutrophil-to-lymphocyte ratio (NLR), platelet-to-lymphocyte ratio (PLR), modified Glasgow prognostic score (mGPS), and prognostic nutritional index (PNI) values in 102 patients with stages 1, 2, and 3A NSCLC were analyzed retrospectively. Results: NLR (p < 0.001), PLR (p = 0.001), PNI (p < 0.001), and mGPS (p = 0.001) variables showed a statistically significant difference according to mortality groups. NLR and PLR values were higher in exitus patients. However, PNI values were higher in surviving patients. NLR (p < 0.001), PLR (p = 0.004), PNI (p = 0.001), and mGPS (p = 0.015) variables showed a statistically significant difference in terms of locoregional recurrence. PNI (p = 0.001) and mGPS (p = 0.001) in terms of distant metastasis development during follow-up and treatment showed a statistically significant difference. Conclusion: NLR, PLR, PNI, and mGPS are easily accessible noninvasive parameters and provide predictive information about survival and disease course. We showed the effect of these parameters on the prognosis. Highlights of the StudyStages 1, 2, and 3A non-small cell lung cancer patients were reviewed retrospectively.Neutrophil-to-lymphocyte ratio, platelet-to-lymphocyte ratio, prognostic nutritional index, and modified Glasgow prognostic score were calculated.We found that these scores were closely related to overall survival, development of distant metastases, and recurrence.Inflammation and nutrition-based scores can be used to predict disease progression and survival.